40Ar-39Ar age constraints on timing of a late hydrothermal event in the Hutti greenstone belt, Karnataka, India. (1st April 2019) - Badhe, Kunda V.; Pandalai, Hari S.; Pande, Kanchan
Graphical abstract: Highlights: 40 Ar- 39 Ar plateau ages of proximal biotite alteration cluster around ∼2.33 Ga and distal sub-surface amphibolite of ∼2.26 Ga to 2.25 Ga. Plateau ages of surface amphibolite rocks of the Hutti greenstone belt ranges ∼2.45 Ga to 2.35 Ga. Hornblende from the Kavital and Yelagatti granitoids yield plateau ages of 2553 ± 13 Ma and 2549 ± 13. Results indicate a significant late-hydrothermal alteration event in the Hutti-Maski greenstone belt. Abstract: Obtaining constraints on the timing of orogenic gold mineralization hosted in shear zones in greenstone belts is often difficult because of the lack of easily datable minerals and problems of overprinting of earlier events of mineralization by later hydrothermal events. In the orogenic Hutti gold deposit the U-Pb SHRIMP date obtained from a monazite grain within arsenopyrite that gave an age of 2547 ± 10 Ma, is generally accepted as the age of early hydrothermal mineralization. Nevertheless, other work has indicated that hydrothermal mineralization may have occurred in later episodes as well. This study reports new 40 Ar- 39 Ar ages for hydrothermal biotite, amphibolite and hornblende in granites that occur along the northern and southeastern boundary of the greenstone belt. The 40 Ar- 39 Ar ages of biotite samples are inferred to be the result of re-setting of the ages of alteration biotite by the last phase of hydrothermal activity in this area at ∼2332 Ma. The study indicates that the effects of the thermal event are more significant in areas of greater hydrothermal access such as within the Hutti shear zone. This late hydrothermal alteration event may be related to the D3 deformational event of Roy (1991). The results of the present work are important because it demonstrates a significant hydrothermal event much after the major 2.58–2.52 Ga accretionary event and accompanying TTG and felsic magmatism in the Eastern Dharwar Craton.